2015
DOI: 10.1111/are.12694
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of formalin, iodine and sodium chloride in improvement of egg hatching rate and fry survival prior to the onset of exogenous feeding in yellow perch

Abstract: Egg disinfection is considered the most important routine work in hatcheries to avoid fungal and/or bacterial infection of fish eggs. The aim of this study was to determine the effectiveness of three disinfectants: formalin, iodine and sodium chloride on the hatching success of yellow perch eggs. The disinfectants were tested in triplicate at different concentrations for 15 and 30 min bath treatments. Two experiments were conducted; formalin at five concentrations (25, 50, 100, 150 and 200 mg L−1) and 25 mg L−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
0
9
2
Order By: Relevance
“…The results of this study showing no decrease in survival associated with the highest formalin concentration differ from those seen by Abd El-Gawad et al (2015). They reported that daily, 15-min 1000 mg/L formalin treatments significantly decreased yellow perch egg survival compared to lowered formalin concentrations of 250 and 500 mg/L.…”
Section: Discussioncontrasting
confidence: 93%
See 4 more Smart Citations
“…The results of this study showing no decrease in survival associated with the highest formalin concentration differ from those seen by Abd El-Gawad et al (2015). They reported that daily, 15-min 1000 mg/L formalin treatments significantly decreased yellow perch egg survival compared to lowered formalin concentrations of 250 and 500 mg/L.…”
Section: Discussioncontrasting
confidence: 93%
“…Higher water temperatures increase formalin toxicity (Piper et al, 1982). Formalin concentrations of greater than 500 mg/L have also been shown to increase fish egg incubation times (Akpoilih & Adebayo, 2010;Abd El-Gawad et al, 2015). However, no differences in hatching times between formalin treatment concentrations in this study were observed.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations